Metaphors as ideological constructs for identity in Malaysian short stories - Ravichandran Vengadasamy (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
This paper illustrates how writers use metaphors as constructs of ideology. The paper is based on a study of two short stories that posit LAND as a metaphor for IDENTITY. Working on a sociological view of ideology, the study employed Lakoff’s Conceptual Metaphor Theory to conduct a cognitive analysis of the concepts and ideas inherent in the metaphors in both short stories. By identifying and explaining the structural mappings that exist between the source and target domains that underlie the metaphors, the paper reveals some of the key concerns and social and cultural beliefs of the writer(s). The relevance of these concerns and beliefs to the general theme of the story and to the theme of nationhood is highlighted in the closing argument.